Does social capital influence the intensity of conservation agriculture adoption among smallholder farmers in Malawi? - Mathanda, H.; Pangapanga-Phiri, I.; Hirpa Tufa, A.; Mangisoni, J.; Alene, A.; Ngoma, H.; Phiri, H.H.; Chikoye, D. (Elsevier, 2025)
Addressing persistent food insecurity requires increased and sustained agricultural productivity in spite of compounding challenges of worsening climate shocks and soil degradation. However, despite numerous initiatives by stakeholders like the Malawian government, along with strong scientific evidence supporting Conservation Agriculture (CA), adoption rates in Malawi remain lower than expected. This study examined social capital as a catalyst for the adoption of CA. It used data from 1512 randomly selected smallholder farmers to investigate how different elements of social capital influenced farmers’ decisions to adopt CA practices. The study findings revealed that social capital elements, namely, group membership and relationships with leadership positively influenced CA adoption. Additionally, factors such as cultivated land size, access to extension services, livestock ownership, and credit availability contributed to the number of CA practices adopted. While the transition to full CA adoption remained limited compared to partial adoption, the study revealed promising trends toward greater uptake. Consequently, these findings highlight the need for agricultural policies that promote farmer organizations, community engagement, and training programs to strengthen social networks and enhance the adoption of CA practices in Malawi.